The Muslim majority : folk Islam and the seventy percent - Hadaway, Robin Dale (B & H Publishing Group, 2021)
More than 70 percent of Muslims worldwide practice folk Islam, a syncretistic mix of theologically orthodox Islam and traditional religious beliefs and practices. The Muslim Majority is unlike many published works on evangelism to Muslims, which argue for either apologetic or contextualized "bridge" approaches. These approaches are often ineffective in reaching adherents of popular Islam. Instead, author and missiologist Robin Hadaway outlines a contextual approach that addresses the unique perspective of popular Islam. Hadaway explains the differences between folk Islam and orthodox Islam and explores best practices for reaching the vast majority of Muslims with the gospel of Jesus Christ.